The Application Domains and Integration of Watermelon and Pumpkin Products into Production - Meliboyev M. F; Ergashev O. K; Isoqjonov A (American Journal of Botany and Bioengineering, 2025)
Melon products, in particular, are obtained by separating the primary and secondary pulp of pumpkin fruits, cleaning them, treating them with ascorbic acid (freezing), drying them using sublimation and convective methods, and grinding them into powder using a grinding machine. The secondary pulp of the product, which has a color property, is used in the garment and textile industry to dye various clothes, fabrics, and yarn products, reducing the cost of finished products by about 1-1.5 times.